2020
DOI: 10.1007/s00216-020-02932-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of methotrexate in spiked human urine using SERS-active sorbent

Abstract: This report is dedicated to determination of anticancer drug methotrexate (MTX) in human urine using surface-enhanced Raman spectroscopy (SERS). Aluminum oxide loaded with silver nanoparticles (AO-Ag) was proposed as SERS-active sorbent and used for solid-phase extraction (SPE) of the analyte and its SERS-based determination (SPE-SERS protocol). MTX has strong SERS signal only in alkaline media that challenges its determination in urine due to strong background signal caused by creatinine. The application of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…57 Additionally, Markina et al were able to detect MTX in spiked human urine using the SERS-active sorbent for solid-phase extraction. 58 Furthermore, Subaihi et al demonstrated that by combining HPLC with SERS-based sensing, it is possible to detect MTX and its metabolite in patient urine samples. 59 Even when combining detection with simple sample preparation, MTX detection with Raman spectroscopy or SERS is challenging, especially when aiming to reach the 0.2 μM detection limit in biological matrices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…57 Additionally, Markina et al were able to detect MTX in spiked human urine using the SERS-active sorbent for solid-phase extraction. 58 Furthermore, Subaihi et al demonstrated that by combining HPLC with SERS-based sensing, it is possible to detect MTX and its metabolite in patient urine samples. 59 Even when combining detection with simple sample preparation, MTX detection with Raman spectroscopy or SERS is challenging, especially when aiming to reach the 0.2 μM detection limit in biological matrices.…”
mentioning
confidence: 99%
“…Recently, Parachalil et al showed the possibility of using a robust size-exclusion filtration technique called centrifugal filtration to process human serum samples for MTX detection in human serum with Raman spectroscopy . Additionally, Markina et al were able to detect MTX in spiked human urine using the SERS-active sorbent for solid-phase extraction . Furthermore, Subaihi et al demonstrated that by combining HPLC with SERS-based sensing, it is possible to detect MTX and its metabolite in patient urine samples .…”
mentioning
confidence: 99%
“…Markina et al developed a method to detect the anticancer drug MTX [74]. Their tests were performed on human urine samples that had been artificially enriched.…”
Section: Drugs Monitoringmentioning
confidence: 99%
“…The simplest one is the adjustment of pH, ionic strength, and/or dielectric constant of the analyzed solution to maximize interaction of analyte molecules with SERS substrate and minimize such interaction for admixtures [3][4][5]. The next approach implies preliminary separation of the analyte by chromatographic separation or by solid-phase/ liquid-liquid extraction [6][7][8]. The last approach is based on modification of SERS substrates by various recognition elements, e.g., by antibodies, aptamers, and molecularly imprinted polymers.…”
Section: Introductionmentioning
confidence: 99%